Validation of Alternative Assesment for Rhythmic Activities in Physical Education - Ruron, Antonius Tuan (Department of Physical Education, Sport, Health and Recreation, 2019)
Rhythmic activity has an effect on balance improvement, physical endurance, strength, cardiovascular endurance, flexibility and increased vital capacity. To support quality learning, an assessment instrument is needed so as to measure what is to be measured. The aim of the study was to examine the validity of the content of alternative assessments for rhythmic activity that have been developed in Physical Education (PE) learning for Junior High School Students. The research method used a method of evaluating the subject of document research. The research subjects were the documents of alternative assessment instrument with three main indicators, namely the level of difficulty of movement, rhythm accuracy, and enthusiasm, with each indicator having three items. Data collection technique used the Delphi technique of 6 experts. Data analysis applied a formula of Content Validity Ratio (CVR) technique developed by Lawshe. The results showed the content validity of alternative assessment instruments, with the indicator of level of difficulty for item one having a CVR value of 0.66, and for item two and three having a CVR value of 1.00. In the indicator of rhythm accuracy, the CVR value on all items was 1.00, and the CVR value of the item on the indicator of enthusiasm was 0.66. Conclusion. All items had CVR value above 0.5, thus alternative assessment items indicated high content validity.